Scheduling sporadic tasks on multiprocessors with mutual exclusion constraints - Easwaran, Arvind (2014)
Consider the problem of scheduling sporadic tasks on a multiprocessor platform under mutual exclusion constraints. We present an approach which appears promising for allowing large amounts of parallel task executions and still ensures low amounts of blocking.